2018
DOI: 10.1055/s-0038-1667007
|View full text |Cite
|
Sign up to set email alerts
|

Otologic Findings Based on no Complaints in a Pediatric Examination

Abstract: Introduction the otological evaluation is highly significant in those branches of medicine in which the general evaluation of the patient is conducted by general practitioners and pediatricians. Objectives To investigate the otologic findings and their incidences in the sample, which consisted of patients who presented to the pediatric outpatient clinic with nonotologic complaints. Methods Patients, aged between 2 and 16 years, who had neither otorhinolaryngological complaints nor history of surgery by the oto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…High frequencies of consultations for hearing and/or speech evaluation in the early and middle childhood may be related to middle ear problems in these ages. Demir et al (3) reported that 12% of 973 children who applied to pediatrics outpatient clinic with non-otorhinolaryngological complaints had external or middle ear disorders including otitis media with effusion (6.9%), impacted cerumen (3.8%) and even congenital cholesteatoma (0.1%).…”
Section: Discussionmentioning
confidence: 99%
“…High frequencies of consultations for hearing and/or speech evaluation in the early and middle childhood may be related to middle ear problems in these ages. Demir et al (3) reported that 12% of 973 children who applied to pediatrics outpatient clinic with non-otorhinolaryngological complaints had external or middle ear disorders including otitis media with effusion (6.9%), impacted cerumen (3.8%) and even congenital cholesteatoma (0.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The early-stage disease may not be associated with complaints such as ear pain, ear fullness, or hearing loss; therefore, otoscopy should be routinely performed by primary care clinicians and not just by otolaryngologists. Half of all children present with ENT complaints, and 67% of all visits to emergency departments by children are EMTrelated [7][8][9]. Thus, as well as otolaryngologists, primary care providers (in pediatrics, and family and internal medicine), and emergency department physicians require otoscopy skills [10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cerumen is usually asymptomatic, but in symptomatic cases, its removal is indicated (Horton, et al, 2020, Michels et al, 2019. In addition, the need for an otological exam (otoscopy or complementary exam) for diagnosis would be another indication for a wax removal procedure (Demir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%